Salivary Glands, Saliva and Oral Findings in COVID-19 Infection - Marlus da Silva Pedrosa; Carla Renata Sipert; Fernando Neves Nogueira (Association of Support to Oral Health Research (APESB), 2022)
The world is under the threat of the novel coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite several efforts to contain the disease spread, it still constitutes a public health emergency of international concern. Several published reports in the scientific literature called attention of the oral cavity as the potential route of infection, the implications for dental practice and the use of saliva in the diagnose of the COVID-19. The aim of this article is to provide an overview of the literature on the salivary glands and saliva in the context of SARS-CoV-2 infection. A brief discussion of taste disturbances and oral findings in COVID-19 patients is also presented.  The literature shows that SARS-CoV-2 could infect the salivary glands. It is not possible, however, to make speculations regarding them as reservoirs for the SARS-CoV-2. In addition, patients with COVID-19 presented several oral repercussions, including hyposalivation and taste disturbances. A few reports showed oral ulcers and blisters associated with SARS-CoV-2 infection. However, it remains not fully understood and might lead to erroneous assumptions. Overall, further studies are necessary to understand the real role of salivary glands and saliva in the context of SARS-CoV-2 infection.